2006
DOI: 10.1021/bi051676f
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Granisetron with an Agonist-Free 5-HT3A Receptor Model

Abstract: A new homology model of type-3A serotonin receptors (5-HT(3A)Rs) was built on the basis of the electron microscopic structure of the nicotinic acetylcholine receptor and with an agonist-free binding cavity. The new model was used to re-evaluate the interactions of granisetron, a 5-HT(3A)R antagonist. Docking of granisetron identified two possible binding modes, including a newly identified region for antagonists formed by loop B, C, and E residues. Amino acid residues L184-D189 in loop B were mutated to alanin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
35
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 31 publications
6
35
0
Order By: Relevance
“…For H185 a substitution to cysteine would also conserve its side-chain interactions as both residues are capable of hydrogen bonding. However, it was previously reported that mutations at this location reduce cell-surface expression, and the lower B max value we measured for granisetron (H185C = 123 ± 23 fmol mg −1 ; wild type = 4843 ± 512 fmol mg −1 ; paired samples, n  = 4) is consistent with this (Joshi et al., 2006, Thompson et al., 2008). For tropisetron it is therefore possible that the absence of binding does not reveal interactions but, given the higher levels of non-specific binding, instead reveals expression levels that are below the threshold for detection.…”
Section: Discussionsupporting
confidence: 92%
“…For H185 a substitution to cysteine would also conserve its side-chain interactions as both residues are capable of hydrogen bonding. However, it was previously reported that mutations at this location reduce cell-surface expression, and the lower B max value we measured for granisetron (H185C = 123 ± 23 fmol mg −1 ; wild type = 4843 ± 512 fmol mg −1 ; paired samples, n  = 4) is consistent with this (Joshi et al., 2006, Thompson et al., 2008). For tropisetron it is therefore possible that the absence of binding does not reveal interactions but, given the higher levels of non-specific binding, instead reveals expression levels that are below the threshold for detection.…”
Section: Discussionsupporting
confidence: 92%
“…How can we decide which docking position is relevant in binding? The docking vicinity of the distal piperazinyl tertiary amino group of compounds 2 and 32 to N128 is in agreement with the docking vicinity of the analogous granatane amino group of granisetron, a 5-HT 3 R antagonist (K i = 0.20 nM) [30], to N128 [27]. Overlapping docking positions of active and inactive derivatives were considered artefacts, while the similar dockings of the active ones support similar binding modes associated with high affinity.…”
Section: -Ht 3a R Modellingsupporting
confidence: 74%
“…This was based on the building of a homology model of 3A -type 5-HT receptors (5-HT 3A Rs), obtained from the electron microscopic structure of the nACh receptor with agonist-free binding cavities at 4 resolution [27]. This was based on the building of a homology model of 3A -type 5-HT receptors (5-HT 3A Rs), obtained from the electron microscopic structure of the nACh receptor with agonist-free binding cavities at 4 resolution [27].…”
Section: -Ht 3a R Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…Docking studies using homology models have found multiple energetically favorable poses of the antagonist granisetron within this binding site, and the orientation of the drug and the identities of the interacting residues are not constant across poses. 1114 For example, Thompson et. al.…”
Section: Introductionmentioning
confidence: 99%